An Overview of Youth Substance Abuse Recovery Strategies in Norway. Issue 4 (1st October 2016) - Gaulen, Zhanna; Carlsen, Siv-Elin Leirvaag
ABSTRACT: There are a number of available adolescent substance abuse treatment centers and services in Norway. The overall responsibility to help youth that need alcohol and/or drug treatment lies in the municipalities. Treatments take place either in institutions (e.g., child welfare institutions or inpatient settings) or at outpatient clinics (e.g., opioid maintained treatment, psychiatric youth team). If the adolescent needs detoxification services, they typically receive this in a hospital or residential treatment setting. This article will describe available opportunities and barriers for youth treatment and aftercare in Norway.